PENDIDIKAN SEKS PERSPEKTIF AL-QUR’AN DAN HADIS - Khoiril Anam; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
Sex education in general is a way (system) or means (tool) to educate, direct or lead other people to behave in good and correct sexual behavior. Sex education is very important to prevent various deviations. This sex education will be more successful if it is accompanied by religious values ​​in sex education. In Islam, sex education is very important and is one of the focuses of education and religious teachings in terms of the Al-Qur'an and Hadith.This article discusses sex education from the perspective of the Koran and Hadith. In Islam, sex education is fundamental and important. Education will direct sexual desire according to Islamic rules to make it one of the main teachings. In the Qur'an, many verses touch on sex, including the protection of eyesight and the protection of the genitals of the opposite sex. As in Surah An-Nur verse 31, And say to the women who believe, that they must guard their eyes, and guard their private parts, and do not reveal their ornaments (genitals), except those that are (normally) visible. And let them cover their headscarves over their chests, and do not reveal their jewels, except to their husbands, or their fathers, or their husbands' fathers, or their sons, or their husbands' sons, or their brothers. , or the sons of their brothers, or the sons of their sisters, or the women of their (fellow Muslims), or the servants they have, or the servants of (old) men who have no desire (for women) or children who don't understand about women's private parts. And let them not stamp their feet so that the jewelry they are hiding will be discovered. And repent all of you to Allah, O believers, so that you will be lucky. The aim of Islamic sex education for teenagers is to provide an understanding of the importance of taking care of their body and psychology. The main thing is to get the right knowledge and be able to prevent adultery which is clearly prohibited by religion and other sexual deviations such as same-sex sexual relations. In other words, sex education can prevent casual sex from occurring